On the Cost-Effective Temporal Allocation of Credits in Conservation Offsets when Habitat Restoration Takes Time and is Uncertain - Martin Drechsler (Environmental and Resource Economics, 2022)
Tradable permits, or offsetting schemes, are increasingly used as an instrument for the conservation of biodiversity on private lands. Since the restoration of degraded land often involves uncertainties and time lags, conservation biologists have strongly recommended that credits in conservation offset schemes should be awarded only with the completion of the restoration process. Otherwise, the instrument is claimed to fail on the objective of no net loss in species habitat and biodiversity. What is ignored in these arguments, however, is that such a scheme design may incur higher economic costs than a design in which credits are already awarded at the initiation of the restoration process. In the present paper a generic agent-based ecological-economic simulation model is developed to explore different pros and cons of the two scheme designs, in particular their cost-effectiveness. The model considers spatially heterogeneous and dynamic conservation costs, risk aversion and time preferences in the landowners, as well as uncertainty in the duration and the success of the~restoration process. It turns out that, especially under fast change of the conservation costs, awarding credits at the initiation of restoration can be more cost-effective than awarding them with completion of restoration.
Keywords: 330; Agent-based model; Conservation offsets; Ecological-economic model; Habitat restoration; Uncertainty